India : Alleviating Poverty through Forest Development - Kumar, Nalini (World Bank, Washington, DC, 2014)
This case study, one of six evaluations in a series of country case studies, aims to understand the implementation of the 1991 Forest Strategy in World Bank operations and to obtain the views of the various stakeholders in the country about the involvement of the Bank. Each country study examines the overall development of the country's forest sector. This naturally includes the environmental impacts on forests, such as degradation, bio-diversity loss, and deforestation as well as encompassing the economic uses of forests, particularly the management of forest resources for production, the role of forest development in poverty alleviation, and the impacts of forest research and development. The report takes a multi-disciplinary approach that discusses economic, social, political, institutional, and financial issues, and is based on evidence from the literature; review of project documents and files; extensive interviews with Bank and other donor agency staff, specialists, forest officials, beneficiaries; and field visits. The report analyzes the interactions among the Bank's country assistance strategy, economic and sector work, policy dialogue, and their lending portfolio. The review is divided into two parts. Part 1 surveys the changing state of the forests in India. It explores causes of change in the extent and the quality of the forest cover. Part 2 explores the World Bank's lending and non-lending activities before and after the Bank's 1991 Forest Strategy.